2016
DOI: 10.1016/j.neuroimage.2016.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe viscoelasticity and relational memory performance

Abstract: Structural and functional imaging studies have been among converging lines of evidence demonstrating the importance of the hippocampus in successful memory performance. The advent of a novel neuroimaging technique – magnetic resonance elastography (MRE) – now makes it possible for us to investigate the relationship between the microstructural integrity of hippocampal tissue and successful memory processing. Mechanical properties of brain tissue estimated with MRE provide a measure of the integrity of the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
113
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 67 publications
19
113
1
Order By: Relevance
“…This concept appears to be much less strong in ξ where the only significant relationship exists between the Am and Hc – both located in the medial temporal lobe – and is unchanged by the consideration of global properties. This may support the sensitivity of ξ that we reported previously for the Hc [Schwarb et al, 2016]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This concept appears to be much less strong in ξ where the only significant relationship exists between the Am and Hc – both located in the medial temporal lobe – and is unchanged by the consideration of global properties. This may support the sensitivity of ξ that we reported previously for the Hc [Schwarb et al, 2016]. …”
Section: Discussionsupporting
confidence: 92%
“…This is especially critical for potential studies of tissue structure and its role in cognitive performance, as the integrity of specific SGM structures is critical in dissociable cognitive processes such as memory [Cohen and Squire, 1980], executive function [Buckner, 2004], and skill learning [Laforce and Doyon, 2001]. In fact, we have previously reported that hippocampal viscoelasticity is strongly associated with behavioral performance on a relational memory task [Schwarb et al, 2016]. …”
Section: Introductionmentioning
confidence: 99%
“…One example in the brain is the hippocampus, which has a volume of around 4 cm 3 for each hemisphere, and plays a crucial role in memory function. Schwarb et al used NLI-MRE to show that lower damping ratio in the hippocampus is strongly correlated with increased performance in memory-related tasks [34], and our study is the first phantom demonstration that damping ratio imaging at these scales is accurate.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, Schwarb et al reported a strong correlation between damping ratio of the hippocampus and memory task performance in a cohort of 20 volunteers which showed, for the first time, a relationship between viscoelastic properties and functional outcomes, as well as changes in hippocampal damping ratio after an exercise intervention in a group of multiple sclerosis patients. [3436] Despite the potential clinical significance of attenuation in these studies, independent measurements are difficult to acquire in vivo. Phantom studies are a vital step in validation of a spatially resolved imaging modality; however, to the best of our knowledge, no images with known attenuation parameter contrasts have been published to date, which undermines confidence in the various MRE processing pipelines to accurately recover spatially distributed parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation